Discipline in Disguise: A Foucauldian Perspective on Agile at Scale - Mohammed M-hasni; Ousama Awad; Aeman Masbah (AlQalam Journal of Medical and Applied Sciences, 2026)
This study critically examines the transformation of Agile methodologies when scaled within large organizations, focusing on frameworks such as SAFe® and LeSS. Originally intended to foster flexibility, autonomy, and collaboration, Agile in its scaled form often reintroduces hierarchical controls, creating what is termed a paradox of “discipline in disguise.” While these frameworks claim to enhance empowerment and adaptability, they frequently institutionalize mechanisms of surveillance and normalization through rituals, metrics, and digital tools. Drawing on Michel Foucault’s concepts of disciplinary power, panopticism, and governmentality, this research analyzes how practices such as daily stand-ups, Agile boards, and coaching roles serve as instruments of subtle control. Findings suggest that transparency mechanisms—such as dashboards and progress metrics—promote self-monitoring and conformity, reducing psychological safety and innovation. Agile coaches further reinforce organizational norms under the guise of facilitation, creating decentralized yet pervasive governance. This paper contributes to critical management studies by reframing scaled Agile as both enabling and constraining. It argues for reflexive implementations that maintain Agile’s core values while mitigating disciplinary tendencies embedded in its structures. The analysis highlights the tension between autonomy and control, urging organizations to preserve adaptability without reinforcing bureaucratic practices.